An analysis of the evolutions of the decorative elements: case study the seven dwellings in Ghadames Old City / Samira Nuri Ben Said - Ben Said, Samira Nuri (Institute of Graduate Studies, UiTM, 2014)
The Old City of Ghadames in Libya, which is today a major tourist attraction, has some old dwellings that contain intricate and meaningful ornamental art. This thesis seeks to investigate these artistic works and decipher their symbolic meanings. This is because, to the modern generation, even of artists and craftsmen, these meanings are lost and these generations-old artefacts are viewed merely as beautiful visual art. This research seeks to solve this problem and the main objectives are (a) to analyse the roots of the selected traditional decorative motifs in the built environment in Ghadames old city of Libya; (b) to uncover the symbolic meanings of these decorative elements found in the architecture in Ghadames old city; and (c) to provide a deeper understanding of the evolution of traditional decorative elements, and symbols found in selected buildings in Ghadames old city in Libya.